2018
DOI: 10.1093/jrr/rry054
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of three-dimensional conformal radiotherapy versus volumetric-arc radiotherapy in cervical cancer treatment: applying the central-shielding principle to modern technology

Abstract: This study evaluated the feasibility of applying volumetric-arc radiotherapy (VMAT) in standard curative radiotherapy for non-bulky cervical cancer using the central-shielding principle. Whole-pelvis irradiation of 20 Gy and central-shielding pelvis irradiation of 30 Gy, both in 2 Gy fractions, were created using 3D conformal radiotherapy (3DCRT) with a standard midline block or VMAT. Composite dose distributions and DVH parameters were compared first in a simple phantom model and then in 10 clinical cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…However, none of these studies applied WPRT-CS, given that they enrolled patients in Western countries. Tamaki et al reported a dosimetric analysis of WPRT-CS using VMAT for UCC as a planning study (26). To the best of our knowledge, this is the first report of the combination of HDR-ICBT and IMRT, which consisted of WPRT and WPRT-CS using TomoTherapy or other IMRT modalities, for UCC patients in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…However, none of these studies applied WPRT-CS, given that they enrolled patients in Western countries. Tamaki et al reported a dosimetric analysis of WPRT-CS using VMAT for UCC as a planning study (26). To the best of our knowledge, this is the first report of the combination of HDR-ICBT and IMRT, which consisted of WPRT and WPRT-CS using TomoTherapy or other IMRT modalities, for UCC patients in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…All patients had stage I-IIB disease with a maximum tumor size <4 cm. Definitions of the CTVs for non-bulky cervical cancer cases were defined and described in a previous report on the application of WP-VMAT and CS-VMAT (10). Briefly, the CTVs for primary disease of the uterine cervix (CTV-PD) and pelvic lymph nodes (CTV-LN) were delineated according to published guidelines (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve standard radiotherapy for cervical cancer in Japan, we previously conducted a dose-planning study which applied IMRT/VMAT to radiotherapy for early-stage non-bulky cervical cancer cases. For CS-EBRT in that study, we re-examined the principle of CS and defined the specific clinical target volume (CTV) of CS-EBRT, a crucial step in the treatment planning of IMRT/VMAT (10). Nonetheless, the original purpose of CS-EBRT, which is to specifically shield the bladder and the rectum, must be maintained in CS-VMAT.…”
mentioning
confidence: 99%
“…All 30 plans were created using PBS with PSAS. In the planning comparison study, 20 patients with NSCHN treated using PBS with PSAS were selected at random from the 30 patients (Table 1) because the majority of previous planning studies used <20 cases [13, 1517], and the findings obtained did not appear to differ markedly between a study using >80 cases and studies using <20 cases [15]. The same contours created by MIM Maestro version 6.5® (MIM Software Inc., Cleveland, OH, USA) were transferred to VQA version 3.0.5® (Hitachi, Ltd, Tokyo, Japan) and iPlan version 4.1® (Brainlab AG, Feldkirchen, Germany).…”
Section: Methodsmentioning
confidence: 99%